Effects of vermincompost application on the population dynamics of Hypogastrura denticulata (Collembola) in an orchard habitat - Abdel-Lateif, H. M. (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Experiments were designed to evaluate the effects of vermicompost application on population abundance, vertical and spatial distribution, and the population age structure of Hypogastrura denticulata (Collembola). In field, experiment was designed on the base of completely randomize samples. Vermincompost treatments at doses of 0, 5, 10, 15 kg/plot were adopted and Collembola densities were estimated four times during 1 year after treatment. A significant effect on the abundance of Collembola in the 15 kg treated plot was observed, where its population abundance was obviously flourished. However, at a dose of 15 kg/plot, intensive vertical migration was recorded. In a vermin compost-free plot, and 5kg vermincompost treated plot Hypogastrura denticulatashowed tendency of less frequent spatial aggregation. The application of vermincompostat the highest dose had a marked influence on the aggregation indices. A slight effect at the dose of 5 kg/plot, on the current reproductionstatuswas observed but no significant effect of that dose comparing with control could be detected. At the high dose of vermin compost (5 kg/plot) the pattern of the frequency distribution curve of different age classes could describe the general characteristic of the expanding population. It is concluded that the vermincompost treatment of 15 kg/plot has a positive effect on the abundance and the development of the test species. Moreover, that Hypogastrura denticulata may serve as bio indicators to evaluate the role of vermincompost application on the soil habitat.